Mechanism of human fertilization - Álvarez Díaz, Jorge Alberto (2015)
We do an updated revision in regards to the current concepts of biology-based early development (combining knowledge of cell biology and molecular genetics), in an accessible way and considering implications of basic science on clinical practice. Didactically we divide the mechanism of human fertilization in several phases: sperm activation, incorporation of the sperm the ovum cytoplasm, metabolic activation of the ovum. pronuclei formation, pronuclei migration, and initiation on of the first cellular division and initial development. Some special considerations are also done regarding the mechanisms al epigenetic regulation in early development, and some implications on biological development in scientific names identifying these stages.